OPBL Learning Model on Problem Solving Ability in Basic Programming Subjects in Vocational High Schools: Model Pembelajaran OPBL Terhadap Kemampuan Pemecahan Masalah Pada Mata Pelajaran Pemrograman Dasar di Sekolah Menengah Kejuruan - Andhita, Krisna; Untari, Rahmania Sri (Indonesian Journal of Education Methods Development, 2023)
Basic Programming subjects are compulsory subjects at SMK 1 Walisongo, especially for the Multimedia major. The purpose of this study is to improve students' problem solving abilities. The research model used is experimental quantitative. The results showed that there was an effect between the pre-test using the problem based learning model with average 76,95 and the post-test using the open problem based learning with average 87,80 that occurred in class X MM as many as 20 students. Teachers pose problems and students solve problems based on their understanding of analysis, with students being given the freedom to present their own arguments through questions about basic programming topics. With the increasing value of learning, open problem-based learning model learning is the right learning model for teachers.